Students’ feedback on exclusive 6-months online teaching during COVID-19 lockdown: a cross-sectional survey - Khilnani, Ajeet Kumar; Thaddanee, Rekha; Khilnani, Gurudas (International Journal of Research in Medical Sciences, 2021)
The corona virus pandemic has disrupted the human activities all across the globe and teaching-learning activity is no exception. In India, the nation-wide lockdown was announced in late March, and since then the main mode of undergraduate (UG) medical teaching has been through online classes. This is an unprecedented situation, both for medical teachers and students. Our institute initiated online classes for UG students from as early as mid-March, 2020. It has been more than 6 months of exclusive online teaching now and it was imperative to get overall feedback from students regarding its impact on their learning. It would provide useful inputs regarding utility, efficacy and opportunities to improvise further.